Thermal behaviour of intercalated 8-hydroxyquinoline (oxine) in montmorillonite clay - Pastre, I. A.; Oliveria, I. D.; Moitinho, ABS; de Souza, G. R.; Ionashiro, E. Y.; Fertonani, F. L. (Kluwer Academic Publ, 2004)
The composite montmorillonite-8-hydroxyquinoline (Swy-1-8-HQ) was prepared by two different processes and studied by using thermogravimetric analysis (TG/DTG and DSC), as well as helpful techniques as fluorescence in the UV-visible region and X-ray diffraction. The composites developed fluorescent appearance, however with quantum poor efficiency and they exhibited distinct TG and DSC thermal behavior. The fluorescence data of spectra associated to the TG/DT curves allowed to suggest that the 8-HQ was present in the composites in two different circumstances: 1 - intercalated in the interlayer spaces (Swy-1-8-HQ2), rigidly associated to the Substrate feasible as a monolayer with the aromatic rings parallel to the silica layer; and/or, 2 - adsorbed on the Surface (Swy-1-8-HQ1), either as a bilayer formation or tilting of the molecules to the silicate layer sheet. All results confirmed above are in agreement with X-ray diffraction patterns, once the interlayer space increases when 8-HQ is incorporated. The experimental results confirm the formation of the composites in agreement with the method used in the preparation.
Keywords: DSC; montmorillonite; oxine; TG/DTG; X-ray diffraction